2005
DOI: 10.1093/intimm/dxh342
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Th2 polarization by OCH is supported by incompetent NKT cell induction of CD40L and following production of inflammatory cytokines by bystander cells in vivo

Abstract: The altered glycolipid ligand OCH is a selective inducer of T(h)2 cytokines from NKT cells and a potent therapeutic reagent for T(h)1-mediated autoimmune diseases. Although we have previously shown the intrinsic molecular mechanism of preferential IL-4 production by OCH-stimulated NKT cells, little is known about the extrinsic regulatory network for IFN-gamma production. Here we demonstrate that OCH induces lower production of IFN-gamma, not only by NKT cells but also by NK cells compared with alpha-galactosyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
1
1

Year Published

2007
2007
2009
2009

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 40 publications
2
54
1
1
Order By: Relevance
“…We have previously shown that OCH, another analog of ␣-GalCer with a truncated sphingosine chain, preferentially induces Th2 cytokines (21)(22)(23). SGL-S23 administered in vivo induces more IFN␥ and less IL-4 compared with OCH and possesses a stronger ability to suppress inflammatory arthritis compared with ␣-GalCer or OCH (Kaieda S, et al: unpublished observations), indicating a unique property of this ligand.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We have previously shown that OCH, another analog of ␣-GalCer with a truncated sphingosine chain, preferentially induces Th2 cytokines (21)(22)(23). SGL-S23 administered in vivo induces more IFN␥ and less IL-4 compared with OCH and possesses a stronger ability to suppress inflammatory arthritis compared with ␣-GalCer or OCH (Kaieda S, et al: unpublished observations), indicating a unique property of this ligand.…”
Section: Discussionmentioning
confidence: 97%
“…IFN␥ was not induced in vivo by either S25 or S27. (23). Therefore, it seemed reasonable that lower initial IFN␥ production by iNKT cells would result in lower induction of IFN␥ at later time points.…”
Section: Biologic Function Of Sgl-s23 In Vitro and In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…␣-GalCer (KRN7000), a strong agonist of type I NKT cells, has been reported to induce high IFN-␥ and IL-4 (37) with a preferential release of Th1 cytokines. OCH, a weaker agonist of type I NKT cells, has been reported to induce a higher ratio of IL-4/ IFN-␥ than ␣GalCer, leading to a suppression of a Th1-mediated autoimmune disease, experimental autoimmune encephalomyelitis (34,36,38). Because we have reported that a Th2 cytokine, IL-13, plays a critical role in the down-regulation of tumor immunosurveillance by NKT cells (10,13), to determine whether the final effect of type I NKT cell stimulation was due to preferential Th1 or Th2 cytokine induction, we stimulated type I NKT cells with either ␣GalCer or OCH.…”
Section: Stimulation Of Type I Nkt Cells Protects From Tumor Growthmentioning
confidence: 99%
“…One of the most intensively studied examples of this is an ␣GalCer analog designated OCH, in which the fatty acid chain has been shortened to C24:0 and the sphingoid base truncated to C9. This analog is a relatively selective stimulator of IL-4 secretion and has pronounced anti-inflammatory effects in NOD mice and other mouse models of autoimmune disease (6,(11)(12)(13)(14)(15). Our earlier studies identified a novel derivative of KRN7000 containing an 11,14-cisdiunsaturated C20 fatty acid (␣GalCer C20:2) as a potent iNKT cell activator that powerfully stimulates production of IL-4 in association with reduced production of IFN-␥.…”
mentioning
confidence: 99%